2008
DOI: 10.2147/aabc.s3624
|View full text |Cite
|
Sign up to set email alerts
|

Identification of significant genes in genomics using Bayesian variable selection methods

Abstract: In the studies of genomics, it is essential to select a small number of genes that are more significant than the others for research ranging from candidate gene studies to genome-wide association studies. In this study, we proposed a Bayesian method for identifying the promising candidate genes that are significantly more influential than the others. We employed the framework of variable selection and a Gibbs sampling based technique to identify significant genes. The proposed approach was applied to a genomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Mice from two N ‐ethyl‐ N ‐nitrosourea (ENU) lines show abnormal, low amplitude voluntary wheel‐running activity patterns. Circadian activity patterns are double plotted for ease of visualization, with each horizontal line representing 48 hours and successive days plotted along the Y‐axis. Wheel revolutions are depicted as black marks on the horizontal lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice from two N ‐ethyl‐ N ‐nitrosourea (ENU) lines show abnormal, low amplitude voluntary wheel‐running activity patterns. Circadian activity patterns are double plotted for ease of visualization, with each horizontal line representing 48 hours and successive days plotted along the Y‐axis. Wheel revolutions are depicted as black marks on the horizontal lines.…”
Section: Resultsmentioning
confidence: 99%
“…There is ample evidence of a genetic basis for the development and manifestation of CFS . Polymorphisms in several genes (eg, the adrenergic receptor a1 ( ADRA1A ), the serotonin transporter ( SLC6A4 ) or receptor ( HTR2A ), tyrosine hydroxylase ( TH ), corticosteroid‐binding globulin ( CBG ), corticotropin releasing hormone receptor 1 ( CRHR1 ), the cytokine IL‐1B, neuronal PAS domain protein 2 ( NPAS2 ), the nuclear receptor subfamily 3; group C, member 1 glucocorticoid receptor ( NR3C1 ) and the glutamate receptor‐ionotropic kinase 2 ( GRIK2 ) have all been linked to either the occurrence or the severity of fatigue symptomology in humans . Furthermore, a recent study comparing CFS patients to healthy controls identified 442 additional candidate genes associated with CFS .…”
Section: Introductionmentioning
confidence: 99%
“…Accounting for models is not a trivial task because even a relatively small set of factors results in the large number of possible models [61]. For example, if we study 10 factors, then these 10 factors yield 2 10 possible models.…”
Section: Data Reduction and Feature Selection Approachmentioning
confidence: 99%
“…The SSVS method has been extended to linear and generalized linear mixed models (Chen and Dunson, 2003; Kinney and Dunson, 2007), and to survival models (Lee and Mallick, 2004). Because of its ability to select among a larger number of potential predictors, it has been applied to high dimensional data including genomics and other complex disease risk factor studies (Beattie et al , 2002; Lee et al , 2003; Swartz et al , 2008; Lin and Huang, 2008). …”
Section: Introductionmentioning
confidence: 99%